Effects of pulsed electric field technology on the nutritional value and biological function of plant food - Su, Wenlong; Wang, Qianxinhong; Li, Jie; Qiu, Zhidong; Qiu, Ye (Frontiers in Sustainable Food Systems, 2024)
Pulsed Electric Fields (PEF) technology is an emerging non-thermal food processing technology that is widely used because of its low damage to food quality and its ability to kill harmful microorganisms in food. The oxidative stress caused by PEF results in the synthesis and accumulation of nutrients, and plant foods stimulated by PEF produce large amounts of Reactive Oxygen Species (ROS), which activate the metabolite synthesis pathway and eventually synthesize proteins, polyphenols, thioglucosides and carotenoids; ROS accumulate in the cell membrane of microorganisms and cause protein expression. The accumulation of ROS in the cell membrane of microorganisms can cause abnormal protein expression, damage the lipid layer and Deoxyribonucleic Acid (DNA), and eventually lead to microbial inactivation. PEF technology in food processing are multifaceted, enhancing both the nutritional value of food through the augmented presence of health-beneficial compounds and ensuring food safety by effectively inactivating harmful microorganisms. This innovative technology stands at the forefront of food processing solutions, promising to fulfill the growing consumer demand for foods that are not only safe and of high quality but also rich in nutritional value. PEF’s role as a cornerstone technology in the food industry heralds a new era of food processing, where nutrition and safety converge to meet the sophisticated needs of today’s consumers.